1977
DOI: 10.1172/jci108812
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Complexes after Renal Transplantation

Abstract: A B S T R A C T To assess the role ofcirculating immune complexes in the pathogenesis of acute rejection, sera were measured for such complexes by the 125I-Clq binding assay in 45 normal subjects, 24 allografted patients undergoing acute rejection, and in 11 allografted patients in a quiescent phase. Increased Clqbinding activity (Clq-BA) was detected in 14 patients with acute rejection, 9 of whom had renal biopsies showing fibrin deposition in the vasculature together with cellular infiltrates in the tubulo-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1981
1981
1986
1986

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…A positive relationship between AR and CICs was re ported by Ooi et al [3], Smith et al [4] and Vincent et al [5], whereas our studies [2] and those of others [6][7][8] failed to demonstrate such a relationship. Ooi et al [3] and Smith et al [4] noted that CICs were present in association with a specific type of Immorally mediated rejections character ized by fibrin deposition in the glomeruli.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…A positive relationship between AR and CICs was re ported by Ooi et al [3], Smith et al [4] and Vincent et al [5], whereas our studies [2] and those of others [6][7][8] failed to demonstrate such a relationship. Ooi et al [3] and Smith et al [4] noted that CICs were present in association with a specific type of Immorally mediated rejections character ized by fibrin deposition in the glomeruli.…”
Section: Discussioncontrasting
confidence: 64%
“…Ooi et al [3] and Smith et al [4] noted that CICs were present in association with a specific type of Immorally mediated rejections character ized by fibrin deposition in the glomeruli. These investiga tions did not find CICs in patients with cell-mediated rejec tion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the discussion of the pathogenetic and diagnostic as well as prognostic value of CICs in autoimmune diseases [7][8][9][10][11][12][13][14], malignant tumors [15][16][17][18][19][20][21][22] and infections [23][24][25][26] their role in connection with kidney allotransplantation has recently attracted wider interest. While Palosuoet al [I] and Haskovà et al [2] succeeded in showing CICs after kidney transplantation but did not describe their associa tion with rejection crises, Ooi et al [3] and Simpson et al [27] described the occurrence of increased serum levels of CICs in connection with acute rejection crises. Our studies carried out on 27 patients and including 17 rejection crises showed no verification of these findings whatsoever.…”
Section: Discussionmentioning
confidence: 99%
“…While in GN patients the positive reactions showed a steady decrease after transplantation, in PN patients we found a decrease only after an immediate postoperative increase. In their recent publication, Ooi et al [3] reported on a significant association between increased values of serum Clq-binding activities (Clq-BA) as determined by a 125I-Clq binding assay and the occurrence of humoral rejection episodes. In contrast to this report, Wegtnüller et al [4] could not observe an association between the presence of CICs and rejection episodes.…”
Section: Introductionmentioning
confidence: 99%